Computing the Value of Pi in the Manner of Lambda Function with R Statistical Programming Language - Muhammad Reza Fahlevi; Mohammad Andri Budiman (Data Science: Journal of Computing and Applied Informatics, 2021)
The value of π is one of the famous mathematical constant, not only to mathematicians, but also to physicists and to engineers. Numerous algorithm is used to compute what is the value of π, but most of programmer do not use lambda function and neglect the aesthetic of their script. This study aims to compute the value π by write it first as infinite series using Riemann sum, and then the computing of it is conducted in R programming language. We involved the role of anonymous function or known as lambda function to make the R code is more beautiful, artistic, and elegant.